Framing strategies of news outlets in the post-2008 general election - Baharin, Muhammad Izawan (2021)
The aftermath of the 2008 general election has shown a series of upheavals in the Malaysian political landscape from multi-culturalism to the demand for greater public participation. Hence, what are the relevance political changes that occurred during the period? Therefore, this study attempts to identify the framing strategies of the news outlets that offer different political tendencies. This study narrows the scope of the investigation by focusing on news coverage of the political manifesto. This study was conducted using the mixed-method involving the content analysis of the news articles and semi-structured interviews with the editors of Utusan Malaysia and Malaysiakini. The results revealed that Utusan Malaysia (N = 261) mainly applied the morality frame while the responsibility frame was dominant in Malaysiakini (N = 151). In other words, the pro-government media highlighted political issues with moral values whereas the news portal emphasized citizen engagement. Both news outlets also relied on thematic frames to address political issues. There is also a positive relationship between the human-interest frame and episodic frames in the reporting of Utusan Malaysia thus suggesting the possibility of the association between the frames. Most of the news in Utusan Malaysia relied on a negative tone, while a positive tone was dominant in Malaysiakini. The semi-structured interviews revealed that the agenda of the organization served as the guideline in presenting political news. The editors admitted they received political instructions but still strove to promote fair reporting within their capacity. Conclusively, this study is able to deepen the understanding of framing strategies and expand the existing knowledge by exploring the associations between frames. The combination of content analysis and semi-structured interviews further assisted the framing practices thoroughly. On a larger scale, the study provides a better understanding of the media agenda, strengths, and boundaries in fulfilling their role.